2020
DOI: 10.1093/ijnp/pyaa050
|View full text |Cite
|
Sign up to set email alerts
|

A Study in First-Episode Psychosis Patients: Does Angiotensin I-Converting Enzyme Activity Associated With Genotype Predict Symptom Severity Reductions After Treatment With Atypical Antipsychotic Risperidone?

Abstract: Background Our previous studies showed increased angiotensin I-converting enzyme (ACE) activity in chronic schizophrenia (SCZ) patients compared to healthy control (HC) volunteers, and the relevance of combining ACE genotype and activity for predicting SCZ was suggested. Methods ACE activity was measured in plasma of ACE insertion/deletion (I/D) genotyped HC volunteers (N = 53) and antipsychotic-naïve first-episode psychosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…Additionally, in our previous work, when assessing PANSS psychopathology, we only determined PANSS scores, while PANSS scores and PANSS factors were also considered in the current study [8,14]. The favorable effect of the ACE-DD homozygous genotype on PANSS depression factor upon antipsychotic treatment, which was observed among female patients in the current study, might be explained by data previously reported by Nani et al [4], indicating that risperidone treatment increases ACE activity, mainly among ACE-DD homozygous individuals (Tables 3 and 4). In this context, the presence of ACE-DD homozygous genotypes may have contributed to the improvements of PANSS positive symptom score and PANSS factor upon antipsychotic treatment among males positive for the ACE-D allele.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Additionally, in our previous work, when assessing PANSS psychopathology, we only determined PANSS scores, while PANSS scores and PANSS factors were also considered in the current study [8,14]. The favorable effect of the ACE-DD homozygous genotype on PANSS depression factor upon antipsychotic treatment, which was observed among female patients in the current study, might be explained by data previously reported by Nani et al [4], indicating that risperidone treatment increases ACE activity, mainly among ACE-DD homozygous individuals (Tables 3 and 4). In this context, the presence of ACE-DD homozygous genotypes may have contributed to the improvements of PANSS positive symptom score and PANSS factor upon antipsychotic treatment among males positive for the ACE-D allele.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, non-adherence to antipsychotic medications was assessed via anamnestic information, and we only assessed a single polymorphism of the ACE gene. Furthermore, in contrast to the previous study assessing the role of ACE-I/D polymorphism in response to risperidone [4], our study comprised patients who were rather heterogeneous regarding antipsychotic medications. Nevertheless, the use of various antipsychotic medications has been shown to affect ACE activity, and there is evidence of both increased ACE activity [51,52] and decreased ACE activity [53] among patients treated with these medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A functional 287-base-pair ACE-insertion/deletion (I/D) polymorphism is the most well-studied genetic alteration that influences ACE expression in humans. ACE-DD homozygous individuals exhibit the highest ACE plasma activity, ACE-II homozygous individuals show the lowest activity, and those who are ACE-ID heterozygous exhibit intermediate activity [ 3 , 4 ]. ACE and angiotensin II have been suggested to play important roles in brain dopaminergic neurotransmission [ 5 , 6 , 7 ]; therefore, the ACE-I/D polymorphism has been investigated in schizophrenia etiology and clinical expression, as assessed using the Positive and Negative Syndrome Scale (PANSS) [ 4 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only sparse data are available regarding the potential association between ACE-I/D polymorphism and antipsychotic treatment. In one study among antipsychotic-naïve first-episode psychosis patients from the Brazilian population, researchers investigated whether ACE-I/D polymorphism-associated changes in plasma ACE activity upon treatment with the antipsychotic risperidone might influence symptom improvement, as measured by total PANSS scores [ 4 ]. Indeed, that group had previously reported increased ACE activity in chronic schizophrenia patients compared to healthy controls, and suggested the potential of using combined ACE genotype and activity for predicting schizophrenia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%